Pengembangan Bahan Ajar Mata Kuliah Pendidikan Pancasila dengan Menggunakan Saintifik Approach Untuk Meningkatkan Kemampuan Berpikir Kiritis: Development of Teaching Materials for Pancasila Education Courses by Using a Scientific Approach to Improve Critical Thinking Ability - Surahman, Harry (Universitas Muhammadiyah Sidoarjo, 2018)
The purpose of this study was to produce textbook products for Pancasila education subjects with a scientific approach. The development model adopted is the 4D model which consists of the stages of define, design, develop, and disseminate. The define phase is a needs analysis for the purposes of preparing an initial draft of textbooks; the design stage is the selection of formats and the preparation of the initial design of textbooks; the develop phase contains textbook validation phase, revision phase 1, individual and small group test, revision phase 2, and real class test through Class Action Research. The variables that will be examined for improvement are increasing the ability to think critically in students. CAR is held for one semester which is divided into two cycles. The process of reporting research results is carried out after the CAR phase and data analysis is complete. Based on the analysis results obtained (1) Development of teaching materials for Pancasila education courses using the Scientific Approach (Scientific Approach) to improve the ability to think critically on students of Indonesian Language Education Study Program, IKIP Budi Utomo Malang has increased. The results of the research in cycle I obtained an average grade of 76.5 included in the good category. Cycle II, obtained an average grade of 83.4 included in the good category. The conclusion of this study is that there is an increase in the average value from cycle I to cycle II of 6.9%.